2008
DOI: 10.2320/jinstmet.72.510
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetostriction of Fe3.2Tb Alloy Film Deposited on Polyurethane Rubber Substrate

Abstract: Magnetostriction and its susceptibility of Fe 3.2 Tb alloy thin film deposited on polyurethane rubber substrate with low deformation resistance by using direct current magnetron sputtering process were investigated. When both residual gas pressure before argon sputtering and sputtering pressure of argon gas (5 N) were less than 5.0×10 -4 Pa and 2.0×10 -1 Pa, respectively, the thickness of the Fe 3.2 Tb films deposited was about 2.96 mm. The giant magnetostriction was found in the Fe 3.2 Tb alloy film on polyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Zhang et al, 2022;Xu et al, 2018;Garcia-Torres et al, 2014;Reisfeld et al, 2009;Reisfeld, 2004) Gadolinium (Gd) (Cai et al, 2020;Fiedler et al, 2007;X. Gao et al, 2022) Terbium (Tb) (Fiedler et al, 2007;Hilder et al, 2008;Reisfeld, 2004;Reisfeld et al, 2003;Rong et al, 2020;Ryszkowska et al, 2007;Su, Zhang, Jia, Gao, Li, Bai, et al, 2019;Suenaga et al, 2008;Sun et al, 2010;Villagra et al, 2021;J. Wang et al, 2013;Xi et al, 2017;Yang et al, 2022;W.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Zhang et al, 2022;Xu et al, 2018;Garcia-Torres et al, 2014;Reisfeld et al, 2009;Reisfeld, 2004) Gadolinium (Gd) (Cai et al, 2020;Fiedler et al, 2007;X. Gao et al, 2022) Terbium (Tb) (Fiedler et al, 2007;Hilder et al, 2008;Reisfeld, 2004;Reisfeld et al, 2003;Rong et al, 2020;Ryszkowska et al, 2007;Su, Zhang, Jia, Gao, Li, Bai, et al, 2019;Suenaga et al, 2008;Sun et al, 2010;Villagra et al, 2021;J. Wang et al, 2013;Xi et al, 2017;Yang et al, 2022;W.…”
Section: Resultsunclassified
“…Yang et al (2022) have contributed to the study of the application of lanthanides as an additive for resistance to degradation by UV radiation, which is attributed to the fluorescence property that terbium compounds possess. Suenaga et al (2008) coated PU with an iron-terbium alloy, analyzing how the material deforms when subjected to a magnetic field. The authors concluded that the sample has a high susceptibility to deformation due to the inherent flexibility of PU.…”
Section: Luminescencementioning
confidence: 99%
“…High-performance thermal management materials should have high thermal conductivities [1][2][3] and low coefficients of thermal expansion (CTEs) for maximizing heat dissipation and minimizing thermal stress and warping, which are critical issues in packaging of microprocessors, power semiconductors, high-power laser diodes, light-emitting diodes (LEDs), and micro-electro-mechanical systems (MEMs) [4][5][6][7]. Thermal stress and warping arise from CTE differences, which become significant in advanced electronic devices because of high heat generated, for example, when highpower laser diodes or high integration level of ICs are in use.…”
Section: Introductionmentioning
confidence: 99%